Sistem Informasi Keuangan Berbasis Website Pada PT Duta Ekspor Globalindo - Azhar Basim Ilhamitamam; Sari Susanti (International Forum of Researchers and Lecturers, 2024)
The rapid development of technology has driven companies to enhance efficiency in their business processes. This development needs to be supported by the use of appropriate and relevant technology to ensure smooth business operations. PT Duta Ekspor Globalindo is a company engaged in export services and requires technology to manage its financial system. Currently, the company still relies on manual methods and Microsoft Excel for financial record-keeping, which can lead to errors, delayed reporting, and security issues. Therefore, this research aims to facilitate the company in managing its financial system by developing a web-based Financial Information System application. The waterfall method, consisting of analysis, design, coding, and testing, was used in the development of the application. The application was built using PHP programming language and MySQL database. The research resulted in the creation of a Financial Information System capable of efficiently managing financial and generating reports.